Changes in nutrition impact symptoms, nutritional and functional status among head and neck cancer patients receiving radiotherapy or chemoradiotherapy at selected hospitals - Neoh, May Kay (2021)
Radiotherapy (RT) or concurrent chemoradiotherapy (CCRT) is the primary treatment for head and neck cancer (HNC). Any loss of weight during RT or CCRT will result in inconsistent radiation to the target region, which may decrease treatment efficacy. The study aimed to determine the changes in nutritional impact symptoms (NIS), nutritional and functional status and their associations with weight loss during treatment (RT or CCRT). This is an observational prospective study with weekly dietitian follow up HNC patients throughout the seven weeks of treatment; NIS, nutritional and functional status of patients were assessed along the treatment. The study subjects were HNC patients who hospitalized undergoing treatment at the National Cancer Institute, Putrajaya. Nutritional status was assessed with the Patient Generated Subjective Global Assessment (PG-SGA) at the baseline and end of the treatment. Head and Neck Symptoms Checklist (HNSC©) evaluated weekly NIS, 24-hour diet recall determined weekly dietary intake and Jamar Dynamometer measured weekly functional status of handgrip strength. Information on sociodemographic and clinical characteristics of the patients was obtained using a structured questionnaire. Data collection was done from March to December 2018. Primary analysis of dietary intake was conducted with Nutritionist Pro software. Statistical data analysis of changes over time was conducted with general linear model of repeated measures using IBM SPSS version 23. Fifty HNC patients, including 39 males (78%) and 11 (22%) females were recruited during data collection. The median age of HNC patients were 60 years old and the age range was 21 to 78 years old. At the end of treatment, the mean weight loss was 4.53 ± 2.87 kg (7.4%) and all patients were malnourished, where 32% were moderately malnourished and 68% were severely malnourished. Muscle mass decreased starting from week 4 (p = 0.002); fat mass and dietary intake decreased starting from week 3 (p=0.022; p <0.001); while oral nutritional supplements (ONS) intake increased from week 3 (p <0.001). At the end of treatment, all HNC patients had xerostomia, altered taste and required ONS. The weight loss percentage was significantly related to change in NIS scores (r = 0.434, p =0.002), indicating the higher NIS score difference during treatment in HNC patients, the greater weight loss percentage. A significant relationship between changes in total energy intake with weight loss percentage was found (r = 0.297, p = 0.036). It can be concluded that intensive nutrition intervention should began before the week 3 of treatment due to a significant change in muscle mass and fat mass. A minimum ONS recommendation of 500kcal starting at baseline, 800kcal at week 2, 1000 kcal at week 3, 1300kcal at week 4, and 1500kcal from week 5 until the end of treatment, by considering any NIS that interferes with eating. A routine biweekly nutrition intervention with NIS monitoring and ONS recommendation is suggested based on the results. Further research by implementing recommendation above should be done in intervention study to improve effectiveness of treatment outcomes by prevent high percentage of weight loss during treatment.